PENGEMBANGAN KINERJA PENGAWASAN PEMILU MELALUI LEADERSHIP DAN KOMPETENSI SDM - Wibowo, Rudi; Syah, Imran; Kumalasari, Aprelia Nur; Minullah, Minullah (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to examine and analyze how the integration of leadership and human resource competencies is implemented within the Election Supervisory Agency (Bawaslu) of East Java Province to improve the effectiveness of election oversight performance. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, non-participatory observation, and institutional document studies. The results show that Bawaslu of East Java Province has systematically implemented the integration of leadership policies and human resource development. This process is implemented through various institutional forums such as plenary leadership meetings, morning roll calls, internal training, and tiered monitoring and evaluation mechanisms. This integration has a positive impact on oversight performance, particularly in terms of reporting consistency, preparedness to deal with disputes, and responsiveness to potential election violations. However, this study also identified challenges such as variations in competency across regions and limitations in training resources.